Tea gardens dipped in local tradition, a community based herbal tea sanctuary located between two previously divided communities - Mistry, Kalpana (My University, 2019)
ing how it is used in traditional cultures with special focus on the local ‘Lenasian’ Indian culture. Concentrating on the various ways it is made, cultivated, types of small scale production and its sensory experiences. Emphasis has been placed on the required infrastructure, specific climate requirements, the sensory experience of local tea culture and its feasibility. Drinking tea has many health benefits, many of which grow stronger with scientific literature being published through modern medicinal research. Tea has been a beverage that is proven to have health promoting properties since the early periods in history. Medicinal research and studies provide evidence and a scientific basis for these ancient beliefs. A deeper investigation into how the properties of tea drinking support medicinal healing benefits strengthen the argument into Indian culture and traditions. Thus a number of healing and meditative spaces are used as programs that complement the cultural links and aesthetics behind tea production and consumption within the context of Lenasia. Emphasis is placed on the philosophies and ideas behind healing spaces, as well as how shapes, materials and forms can be derived to complement the psychological and vitality of healing. The effect of this research and project is to create a tea sanctuary in Lenasia that aims to infuse the ideas behind the consumption of Indian tea, with the surrounding local Indian cultures and traditions. The sanctuary will have a specific focus on the natural (herbal) medicinal and therapeutic practices, how they can be instilled within the local Indian traditions and act as a catalyst to bring a therapeutic and recreational character to the area. A series of structures within the landscape will aim to complement the existing history of the area, green houses will be proposed to grow the tea and form the backbone to the array of social activities on offer. Tea is the second most consumed drink in the world, after water. It has an extensive history behind it which has grown to connect a variety of people and their cultures throughout the world. There is a special connection between the tradition of drinking tea and the local Indian community within Lenasia. It would be great if we could use the ideas behind tea drinking traditions and its history as a way to celebrate Indian culture in Lenasia and bring attention as well as an identity to the local community.
Keywords: Tea; Natural foods; Tea trade